2005
DOI: 10.1680/muen.2005.158.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Community involvement in planning: finding a happy medium

Abstract: In this paper, recent changes in the emphasis on involving the community in planning are discussed. Their implications for professionals and their practice are considered. In particular, the concepts of inclusiveness and representativeness are explored and contrasted. Beyond the initial conclusion that the new planning agenda will demand more time and effort to be put into the involvement process, further inferences are made about the role of the professional changing towards one of facilitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…If the public are given all the necessary information and time within the planning process, they will reach conclusions that experts would have difficulty overruling (Cohen, 2005). The building of the Northside Bridge provided CCC with the opportunity to consult the public over 2 years and explain the issues involved in building infrastructure.…”
Section: Discussionmentioning
confidence: 99%
“…If the public are given all the necessary information and time within the planning process, they will reach conclusions that experts would have difficulty overruling (Cohen, 2005). The building of the Northside Bridge provided CCC with the opportunity to consult the public over 2 years and explain the issues involved in building infrastructure.…”
Section: Discussionmentioning
confidence: 99%
“…Determining how to address such a response, such as how to incorporate it into the design or plan-making process, is a potentially challenging but important issue. Ignoring negative responses is an easy way to antagonise those who participated (Cohen, 2005). Several of the residents' groups in the study reported disillusionment and disappointment with past consultation exercises on planning, development and car parking matters.…”
Section: The Tendency For Views To Changementioning
confidence: 92%
“…For Cohen (2005) they are a useful mechanism for collecting views in the early stages of a development project prior to the production of tangible proposals. For Batheram et al (2005) they allow the exploration of conflicting views and the resolution of disputes.…”
Section: Focus Groupsmentioning
confidence: 99%
See 1 more Smart Citation